Construction of High-Performance Membranes for Vanadium Redox Flow Batteries: Challenges, Development, and Perspectives - Tan Trung Kien Huynh; Tong Yang; Nayanthara P S; Yang Yang; Jiaye Ye; Hongxia Wang (Nano-Micro Letters)
Highlights Critically analyses the ion transport mechanisms of various membranes and compares them and highlights the challenges of membranes for vanadium redox flow battery (VRFB). In-depth analysis and discussion of the best strategies for membranes to achieve high-performance VRFB. Prospective approaches to realising high-performance, sustainable VRFB membranes.